Perspectives Of Local Communities On Nature Conservation In Taman Negara Pahang, Malaysia And Khao Yai National Park, Thailand - Teh, Kate Yng (2017)
This comparative study examines local communities’ perspectives on nature conservation in Taman Negara Pahang, Malaysia and Khao Yai National Park, Thailand. By comparing two different countries with the differences in religions, cultures and traditions, this study also seeks to discover the contributing factors that shape the local people’s views on conservation activities surrounding Kuala Tahan and Khao Yai. The problem statements of this research have acknowledged the parkpeople conflicts as the key challenges to effective park management. Moreover, very little work has been documented by the past researchers about the nature conservation, local people and communication strategies in Malaysia and Thailand. Therefore, this thesis contributes to fill in the gap by exploring the park-people interaction and communication approaches in order to propose a strategic communication framework for both national parks to achieve conservation goals and to solve the conflicts.